Anxiety and depression seem less common in patients with autoreactive chronic spontaneous urticaria. (29th July 2013) - Weller, K.; Koti, I.; Makris, M.; Maurer, M.
Summary Chronic spontaneous urticaria (CSU) is a common and disabling skin disease which is often associated with psychiatric comorbidities such as anxiety and depression. These conditions are widely thought to cause, drive and/or maintain CSU, and have been reported as making an important contribution to the low quality of life in patients with CSU. Almost half of all patients with CSU have autoreactive CSU which can be readily diagnosed by the autologous serum skin test. The prevalence and effects of psychiatric comorbidities in this important subgroup are largely unknown. We carried out a study on two groups of patients with CSU, and found that the anxiety and depression scores were lower in patients with autoreactive CSU than in those with nonautoreactive CSU, the first such finding, to our knowledge. In addition, we found that patients with autoreactive CSU were less likely to have Hospital Anxiety and Depression Scale scores indicative for anxiety or depression compared with patients with nonautoreactive CSU. Our results support the view that autoreactive CSU represents a distinct CSU subgroup with a different disease pattern and a lower rate of psychiatric comorbidities.